Morphology and molecular phylogeny of the marine diatom Nitzschia dentatum sp. nov. and N. johorensis sp. nov. (Bacillariophyceae) from Malaysia (Bangladesh Journal of Plant Taxonomy, 2017)
The marine diatom Nitzschia dentatum sp. nov. isolated from seawater samples of Kudat and N. johorensis sp. nov. isolated from beach sand samples of Sibu Island, Malaysia, have been described in this paper. Morphological identification, molecular phylogeny and toxin analyses were executed on the pure non-axenic algal cultures designated as KD89 and PS8, respectively. The main distinguishing feature of N. dentatum sp. nov. compared to other species is the jaggedcingulum structure which is only unique to this species. Meanwhile, N. johorensis sp. nov.is strongly characterized by the ‘hantzschioid’and ‘nitzschioid’ symmetry dimorphisms; a common diagnostic feature but rarely described in other Nitzschia species. Identification of both strains was made based on the frustule diagnostic features and verified using the partial large ribosomal subunit DNA sequences. The results have confirmed that these two speciesare independent entities and novel species that have not been documented elsewhere. A notable finding from the Maximum Likelihood (ML), Maximum Parsimony (MP) and Bayesian Index (BI) analyses have also revealed that Nitzschia species that have indentation in the middle of valves have been consistently grouped as same clade with high bootstrap values. The extracts of both species did not show detectable amount of domoicacid and have therefore, been classified as non-toxic. This discovery contributes to the documentation of Nitzschia species worldwide.Bangladesh J. Plant Taxon. 24(2): 183–196.